Inovasi Bahan Ajar Teks Debat Berbasis Etnis Batak Toba dengan Bantuan Aplikasi pada Siswa Kelas X SMKS Tarbiyah Islamiyah - Ellyas, Aqiela Reanaldis; Rita, Rita; Kartika, Rika (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2024)
This study aimed to develop and test the feasibility of Toba Batak ethnic-based debate text teaching materials enhanced with applications for class X students at SMKS Tarbiyah Islamiyah. Using the 4D R&D model by Thiagarajan (1974), the research involved 55 students, with a sample of 28 from class X Accounting-1. Data collection included questionnaires, observations, and interviews. Results indicated that the teaching materials were highly feasible, with material experts scoring them 94% ("very valid"), design experts 93% ("very valid"), and Indonesian language teachers 95% ("very valid"). Feasibility was tested in limited and extensive trials, with students scoring the materials 90% ("highly feasible") in the limited trial and 91.6% in the extensive trial. These results conclude that Toba Batak ethnic-based debate text teaching materials, supported by applications, are valid and appropriate for use in the learning process.